The relationship between L2 students’ writing experiences and their perceived poetry writing ability - Liao, Fang-Yu (Studies in Second Language Learning and Teaching, 2017)
This paper looks at how L2 students’ writing experiences relate to the way they think they can write poems and to further investigate if any types of writing experiences contribute to their perceived poetry writing ability. The paper starts by bringing up the value of introducing poetry writing to L2 students. Then, the literature review section highlights the characteristics of L2 poetry and the values of writing poetry in L2 writing classrooms. For the methodology, semi-structured interviews were used to elicit the participants’ understanding of their writing experiences. Additionally, a rating scale was used for the participants to identify their perceived capability of writing poetry. All 18 participants who were from regions that included countries from Eastern Asia, Middle East, or Africa, were L2 students from an M.A. TESOL program located in the USA. Through a hierarchical cluster analysis, the findings categorized these students as having five different types of writing experiences. Through a Pearson correlation test, the researcher also examined if any of the specific writing experiences were found to correspond either positively or negatively with the perceived poetry writing ability. The data suggest that if students recall more grammar and structured writing experiences, they are more inclined to perceive that they have a lower perceived poetry writing ability. Finally, the study seeks to contribute to educators’ understanding about the potential of poetry writing instruction in L2 writing classrooms. It can trigger the exploration for L2 students to find their own personal purposes of writing as multilingual writers.